THE CONCEPT OF BUSINESS ETIQUETTE AND BUSINESS COMMUNICATION - Абдуллажонова Шахноза Акбаровна; Пайзиева Нигина Тургунбой кизи (American Journals, 2023)
This article provides information on the topic "Business etiquette: personal and written communication". The types and principles of business communication are given.
Keywords: Business etiquette, business conversation. written